In Silico Molecular Docking of Flavonoids from Vitex trifolia L. Leaves as Potential Inhibitors of EGFR Double Mutations - Iskandar Yusri; Muammar Fawwaz; Audia Triani Olii (Pharmaceutical Reports, 2026)
The Legundi plant (Vitex trifolia L.) is known to contain flavonoid compounds that exhibit potential anticancer activity through the inhibition of cancer cell growth. This study aimed to evaluate the binding affinity of flavonoid compounds from Vitex trifolia L. leaves against the epidermal growth factor receptor (EGFR) with double mutations (L858R/T790M) using a molecular docking approach. An in silico study was conducted by docking flavonoid compounds with the EGFR protein (PDB ID: 3IKA) using the AutoDock Vina program. A total of 14 flavonoid compounds were analyzed to assess their binding affinity and interaction profiles. The docking results revealed that the compound 2-(2,4-dimethoxyphenyl)-7-hydroxy-5-methoxy-2,3-dihydro- 4H-chromen-4-one (C18H18O6) exhibited the lowest binding free energy, indicating the strongest affinity toward the target receptor. Furthermore, the interaction analysis showed that this compound formed multiple types of interactions with the EGFR active site, including hydrogen bonds, hydrophobic interactions, van der Waals forces, and ionic interactions. These findings suggest that flavonoid compounds from Vitex trifolia L. have potential as inhibitors of EGFR double mutations and may serve as promising candidates for further development as anticancer agents.